'Hard-Copy Rumours': Print Media and Rumour in Indonesia. (March 2015) - Herriman, Nicholas
Many scholars have analysed media and communications in Indonesia by focusing on state control and resistance to it. Another approach emphasizes the press and society interacting. This paper analyses rumours spreading through East Java in October and November 1998, which held that 'ninjas' were targeting traditionalist Muslims, their leaders, preachers and the whole community. The author argues that these rumours developed through the interplay of the newspapers and local gossip.